2020
DOI: 10.2147/dddt.s233174
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long-Term Safety of a Novel Angiotensin Receptor Blocker, Fimasartan, According to the Absence or Presence of Underlying Liver Disease in Korean Hypertensive Patients: A Prospective, 12-Month, Observational Study</p>

Abstract: Purpose: Fimasartan, the ninth and most recent angiotensin receptor blocker (ARB) approved by the Korea Food and Drug Administration, has shown similar efficacy and safety profiles compared to other ARBs. However, due to being predominantly excreted by the hepatobiliary system, concerns on safety have been raised regarding its use in patients with underlying liver disease. Patients and Methods: This prospective, 12-month, observational study evaluated patients with essential hypertension (HTN) receiving ≥1 dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Because of its non-renal pharmacodynamic characteristics, using fimasartan initially raised concerns about hepatic dysfunction, but previous studies showed that the long-term safety of fimasartan did not differ according to the cause of underlying liver disease. 18 Nonetheless, the significant ALT elevation rates were consistently higher in the fimasartan group in a dose-dependent manner ( Supplementary Table 3 ). Moreover, 11 of the 20 patients with DILI in this study were taking fimasartan ( Table 3 ).…”
Section: Discussionmentioning
confidence: 88%
“…Because of its non-renal pharmacodynamic characteristics, using fimasartan initially raised concerns about hepatic dysfunction, but previous studies showed that the long-term safety of fimasartan did not differ according to the cause of underlying liver disease. 18 Nonetheless, the significant ALT elevation rates were consistently higher in the fimasartan group in a dose-dependent manner ( Supplementary Table 3 ). Moreover, 11 of the 20 patients with DILI in this study were taking fimasartan ( Table 3 ).…”
Section: Discussionmentioning
confidence: 88%